2013
DOI: 10.4103/1596-3519.112399
|View full text |Cite
|
Sign up to set email alerts
|

Risk of sensorineural hearing loss in infants with abnormal head size

Abstract: Microcephalic infants should be routinely screened for potential hearing loss particularly where universal newborn hearing screening is not immediately practicable. Etiological investigation of abnormal head size in this and similar population is warranted. Routine screening and maternal immunization for congenital infections should also be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…24 Another study assessed auditory function in microcephaly with high risk for sensorineural hearing loss. 25 Data reported in the literature regarding ZV-associated microcephaly in children are restricted to postnatal hearing loss. 26 The objective of this research was to analyze the BAEPs in children with ZV-associated microcephaly, thus studying the brainstem function and its dependence on chronological age and cephalic perimeter.…”
mentioning
confidence: 99%
“…24 Another study assessed auditory function in microcephaly with high risk for sensorineural hearing loss. 25 Data reported in the literature regarding ZV-associated microcephaly in children are restricted to postnatal hearing loss. 26 The objective of this research was to analyze the BAEPs in children with ZV-associated microcephaly, thus studying the brainstem function and its dependence on chronological age and cephalic perimeter.…”
mentioning
confidence: 99%
“…Although limited data suggests high prevalence of congenital CMV infection (cCMV) in developing countries with high maternal CMV seroprevalence, the burden of disease and natural history of congenital CMV infection (cCMV), especially sub-Saharan Africa, have not been well defined [1,3-5]. Additionally, the role of cCMV in PCEHL in the African continent has not been examined although infants with microcephaly have been reported to be significantly at-risk for PCEHL in Nigeria [6]. Early identification of infants with cCMV allows for prompt detection of children at risk for PCEHL requiring appropriate intervention during critical stages of language development [1,2].…”
mentioning
confidence: 99%
“…Olusanya BO etal study showed increase risk of hearing loss in microcephaly children. 5 Otoacoustic emissions were absent in 19(43.2%) in right ears, present in 9(20.5%) children and on left ear OAE was absent in 16(36.4%). Study done by Anju et al showed 16.9% hearing loss in microcephaly children with delayed development.…”
Section: Discussionmentioning
confidence: 92%